Detection of Human Papillomavirus Type 2 Related Sequence in Oral Papilloma - Taihei Yamaguchi; Masanobu Shindoh; Akira Amemiya; Nobuo Inoue; Masaaki Kawamura; Hiroshi Sakaoka; Masakazu Inoue; Kei Fujinaga (Analytical Cellular Pathology)
Oral papilloma is a benign tumourous lesion. Part of this lesion is associated with human papillomavirus (HPV) infection. We analysed the genetical and histopathological evidence for HPV type 2 infection in three oral papillomas. Southern blot hybridization showed HPV 2a sequence in one lesion. Cells of the positive specimen appeared to contain high copy numbers of the viral DNA in an episomal state. In situ staining demonstrated virus capsid antigen in koilocytotic cells and surrounding cells in the hyperplastic epithelial layer. Two other specimens contained no HPV sequences by labeled probe of full length linear HPVs 2a, 6b, 11, 16, 18, 31 and 33 DNA under low stringency hybridization conditions. These results showed the possibility that HPV 2 plays a role in oral papilloma.